LIQUIDITY AND THE BUSINESS CYCLE: EMPIRICAL EVIDENCE FROM THE GREEK BANKING SECTOR - Vogiazas, Sophocles; Alexiou, Constantinos (Economic Annals, 2013)
In the aftermath of the global financial turmoil the negative market sentiment and the challenging macroeconomic environment in Greece have severely affected the banking sector, which faces funding and liquidity challenges, deteriorating asset quality, and weakening profitability. This paper aims to investigate how banks’ liquidity interacted with solvency and the business cycle during the period 2004-2010. To this end a panel of 17 Greek banks is utilized which, in conjunction with cointegrating techniques and one-way static and dynamic panel models, explores the presence and the strength of the relationship between banks’ liquidity and the business cycle, while allowing for the role of banks’ solvency. Addressing the liquidity risk of the Greek banking sector and the liquidity-solvency nexus remains largely an uncharted area. The results generated provide clear-cut evidence on the linkages between banks’ market liquidity and the business cycle, as reflected in the real GDP and the effective exchange rate. Yet the results display a transmission channel that runs from banks’ solvency to liquidity and from country risk to bank risk.